The legume information system and associated online genomic resources. Issue 3 (4th February 2021) - Berendzen, Joel; Brown, Anne V.; Cameron, Connor T.; Campbell, Jacqueline D.; Cleary, Alan M.; Dash, Sudhansu; Hokin, Samuel; Huang, Wei; Kalberer, Scott R.; Nelson, Rex T.; Redsun, Sven; Weeks, Nathan T.; et al.
Abstract: The Legume Information System (LIS; https://legumeinfo.org ) houses genetic and genomic data, integrated in various online tools to allow comparative genomic analyses. The website and database maintain data for more than two dozen species, particularly focusing on crop and model species and holding data for other diverse species of taxonomic interest. Major analysis features include genome browsers, sequence‐search tools, legume‐focused gene families and a phylogenetic tree viewer, a gene annotation service (which places a submitted gene into a gene family and phylogenetic tree), an interactive microsynteny and pan‐genome viewer, a novel viewer of genetic variant data, genetic maps and viewers, a Data Store for data sets such as assemblies and annotations, InterMine instances for querying genetic and genomic data, and a tool for viewing geographic distributions of germplasm accessions. LIS also integrates with several other legume data resources and tools, including PeanutBase (https://peanutbase.org ), SoyBase (https://soybase.org ), Medicago Hapmap (https://medicagohapmap2.org ), Alfalfa Breeder's Toolbox (https://alfalfatoolbox.org ), and the Legume Federation (https://legumefederation.org ).